Digital Divide or Digital Provide? Technology, Time Use and Learning Loss during COVID-19 - Niaz Asadullah; Anindita Bhattacharjee (Institute of Labor Economics (IZA), 2022)
COVID-19 school closure has caused a worldwide shift towards technology-aided home schooling. Given widespread poverty in developing countries, this has raised concerns over new forms of learning inequalities. Using nationwide data on primary and secondary school children in slum and rural households in Bangladesh, we examine how learning time at home during the early months of school closure varies by access to technology at home. Data confirms significant socio-economic and gender divide in access to TV, smartphone, computer and internet among rural households. However, the analysis of daily time use data shows only a modest return to technology in terms of boosting learning time at home. Learning-grade gradient is shallow and insensitive to TV, smartphone and computer access at home. We also find no evidence that technology access per se helps learning continuity through boosting time spent in online schooling and private supplementary coaching/tutoring. While technology access matters in households where parents act as home tutors, the magnitude of such complementary effect is not large. The results imply a loss of out-of-school learning time during school closure even in households with technology access. We consider additional hypotheses relating to institutional and socio-economic barriers to home-based learning in developing countries.
Keywords: D10; I21; J22; Q50; 330; home-based education; learning crisis; COVID-19; school closure